A road to specialised translation: how to manage a general translation course (spanish > english) - Godoy Tena, Francisco (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The translation process constitutes an essential part in every translator’s professional training. Translation students should be familiarised with several textual genres of different difficulties. The aim of this study is to show the importance of including semi-specialised texts in general translation subjects. To do so, a selection of semi-specialised texts was included together with more general topics. Thanks to this, translation students can learn how to deal with general and semi-specialised documents by giving their critical views in a cooperative environment. They additionally improved in the correct use of translation techniques in both types of text.